2022
DOI: 10.3389/feart.2022.958315
|View full text |Cite
|
Sign up to set email alerts
|

Raw material base of Russia’s unconventional oil and gas reserves (hydrocarbons shale strata)

Abstract: One of the most controversial and discussed issues related to the development of the hydrocarbon raw material base in recent years is the issue of exploring the possibilities of involvement in industrial development accumulations associated with high-carbon shale complexes that are widespread in Russia. Interest therein is supported by the system of benefits provided by the Government for low-permeability reservoirs and special preferential conditions for geological exploration provided to subsurface users in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…At the same time, the total amount of oil in the free pore space of the domanik horizon using kinetic spectra amounted to 10.5 billion tons of oil and 6.3 trillion m 3 of gas, and taking into account the reservoir space defined with the division into the shelf zone, the slopes of the carbonate platform (side parts of the depression) and in the de-pressions is 5.2 billion tons of o.e. in the areas of high concentration, which is comparable to the volume of accumulated HC in traditional reservoirs, estimated in TP about (6 billion tons) and allows to consider the high-carbon domanik strata as an important reserve for oil production in the conditions of high prices for hydrocarbons in the well-developed regions of the European part of Russia (8,11).…”
Section: Discussion Of Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…At the same time, the total amount of oil in the free pore space of the domanik horizon using kinetic spectra amounted to 10.5 billion tons of oil and 6.3 trillion m 3 of gas, and taking into account the reservoir space defined with the division into the shelf zone, the slopes of the carbonate platform (side parts of the depression) and in the de-pressions is 5.2 billion tons of o.e. in the areas of high concentration, which is comparable to the volume of accumulated HC in traditional reservoirs, estimated in TP about (6 billion tons) and allows to consider the high-carbon domanik strata as an important reserve for oil production in the conditions of high prices for hydrocarbons in the well-developed regions of the European part of Russia (8,11).…”
Section: Discussion Of Resultsmentioning
confidence: 89%
“…The estimation of the proportion of syngenetic and epigenetic bituminous in the generation thickness was compared with the effective porosity, i.e. a combined volume method and an improved volume-genetic method were used (Table 3, Figure 19) (8).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Dzungarian basin, a fairly low geothermal gradient is observed in a number of wells in the central part of the basin (2.0 °C-2.3 °C/100 m), and accordingly, conditions for the formation of oil have been preserved at depths up to 6 km, and condensate at deeper depths. Thus, in the work (Prischepa et al, 2022), a pattern of decreasing the density of crude oil with depth was revealed (at a depth of <3,100 m-average density oil 0.84-0.9 g/cm 3 , at a depth of 3,100-3,900 m-light oil 0.8-0.82 g/cm 3 , and below 4,400 m-mainly condensate. An important pattern is noted in the distribution of gas in the central part of the Dzungarian basin.…”
Section: The Influence Of Paleotemperature On the Phase State Of Hydr...mentioning
confidence: 85%
“…The potential of shale oil and gas resources within these rocks is determined via residual hydrocarbons [16]. The assessment of residual hydrocarbons plays a crucial role in evaluating shale oil and gas resources and selecting exploration prospects [17][18][19]. Previous studies suggest that the Ediacaran Dengying Fm acted as a reservoir in the Sichuan Basin.…”
Section: Introductionmentioning
confidence: 99%